The Influence of Fashion Trend and Socialization on Consumptive Lifestyle - Nurul Awalinah Nadiyah; Syuhada' Syuhada'; Ahmad Munir Hamid (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
This study aims to determine: 1) The influence of fashion trends on consumptive lifestyles for female students, 2) The influence of associations on consumptive lifestyles for female students, 3) The influence of fashion trends and associations on consumptive lifestyles for female students. This study focuses on the consumptive lifestyle of female students at Darul Ulum Lamongan Islamic University. The population in this study was 46 female students in the 2022/2023 school year. The sampling technique in this study is a nonprobability sample using saturated sampling due to the relatively small population. The data collection technique used a questionnaire which contained 19 statement items which were measured using a Likert scale of 1 to 5 and tested by validity and reliability. Data analysis techniques to answer the hypothesis using multiple linear regression analysis. Research results: From the partial test it was found that the fashion trend variable (X1) has a significant effect on consumptive lifestyle (Y) because T count > T table or 5.062 > 2.017. If the fashion trend increases the level of consumptive lifestyle, it can be concluded that H1 is accepted or in other words that the fashion trend variable has a significant influence on the consumptive lifestyle. Then from the social variable (X2) it has a significant effect on the consumptive lifestyle (Y) because T count > T table or 4.519 > 2.107, if the association makes the consumptive lifestyle increase, it can be concluded that H2 is accepted or in other words that the social variable has a significant influence significantly to the consumptive lifestyle of female students at Darul Ulum Lamongan Islamic University. The R square value indicates that 78.1% of the consumptive lifestyle variables can be explained by all the variables used in this study, namely fashion trends and association. Meanwhile, 21.9% of the consumptive lifestyle variables are explained by other variables not observed in this study.